RESPON GURU DAN SISWA TERHADAP PEMBELAJARAN PERMAINAN BOLAVOLI YANG DILAKUKAN DENGAN PENDEKATAN MODIFIKASI (PADA SISWA KELAS V SDN WATESWINANGUN I SAMBENG-LAMONGAN) - HIDAYATI, NURUL (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical education in school has important role for education as a whole. The existence of physical education in school is not only to increase children’s healthiness and fitness, but also give cognitive, affective, and psychomotor experience.The main focus of physical education teaching is how to make students feel happy in doing moving activities so it can be optimized.The teaching method done was like what adults did, so students have difficulties in doing the movement. For example, elementary students were given volley ball serve with the size of the court, ball, and net height used by adults. So elementary students followed that rule did not enjoy it and had difficulties in joining sport. Response shows when there is object to be observed, attention to observation object and there are senses as the capture of the object being observed. There are several factors determining the emergence of response : experience, learning process, the level of individual experience, and personality value. The goal of the research is to describe teacher’s and students’ response toward the teaching of physical education done by using modification approach in volley ball game at grade 5 students Wateswinangun I elementary school Sambeng-Lamongan. The conclusions of the research are : 1) The score from question no 1 is 59,3% categorized as agree, question no 2 is 69% said very agree, question no 3 is 41% said agree, question no 4 is 72% said very agree, question no 5 is 75% categorized as agree,  on question no 6 is 84,3% said agree, no 7 is 53,1% said agree, no 8 is 3,12% said agree, questions no 9 is 9,4% said agree, question no 10 is 3,12% said agree. Thus, it can be concluded that teacher’s and students’ response toward physical education teaching through modification approach is categorized as agree. Keywords: Response, Volleyball, Game, and Modification.